Occlusal sequalae of the loss of first permanent molars among children and adolescents. - Kallos Henrietta Hilda; Markovics Emese Rita; Pop Silvia Izabella; Mártha Krisztina I. ("George Emil Palade" University of Medicine, Pharmacy, Science, and Technology of Targu Mures, 2020)
Objective: The purpose of the present study is to evaluate the disintegration of the contact point system, the occlusal changes, and the masticatory force following the loss of the first permanent molars (FPM).